2014
DOI: 10.1126/science.1258966
|View full text |Cite
|
Sign up to set email alerts
|

Sulfate was a trace constituent of Archean seawater

Abstract: Dissecting ancient microbial sulfur cycling Before the rise of oxygen, life on Earth depended on the marine sulfur cycle. The fractionation of different sulfur isotopes provides clues to which biogeochemical cycles were active long ago (see the Perspective by Ueno). Zhelezinskaia et al. found negative isotope anomalies in Archean rocks from Brazil and posit that metabolic fluxes from sulfate-reducing microorganisms influenced the global sulfur cycle, including sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
204
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(216 citation statements)
references
References 66 publications
6
204
2
4
Order By: Relevance
“…Bradley et al (2016) showed that sulfate reducers suppress the discrimination against heavier sulfate isotopes when sulfate concentrations in their environment fall below strain-specific concentration thresholds. A sulfate threshold of ∼200 µmol L −1 was suggested for natural communities of bacterial sulfate reducers (Habicht et al, 2002), but has recently been challenged by the report of substantial isotope fractionation between sulfate and sulfide at sulfate concentrations in the range of 5-10 µmol L −1 in the chemocline of ferruginous Lake Matano (Crowe et al, 2014). Isotope fractionation between sulfate and sulfide in natural environments may, however, also result from disproportionation processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradley et al (2016) showed that sulfate reducers suppress the discrimination against heavier sulfate isotopes when sulfate concentrations in their environment fall below strain-specific concentration thresholds. A sulfate threshold of ∼200 µmol L −1 was suggested for natural communities of bacterial sulfate reducers (Habicht et al, 2002), but has recently been challenged by the report of substantial isotope fractionation between sulfate and sulfide at sulfate concentrations in the range of 5-10 µmol L −1 in the chemocline of ferruginous Lake Matano (Crowe et al, 2014). Isotope fractionation between sulfate and sulfide in natural environments may, however, also result from disproportionation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Seawater sulfate levels in the Archaean Eon (before 2.5 billion years ago) are estimated to <0.01% of modern seawater, probably restricting biological productivity (Crowe et al, 2014), while estimated atmospheric methane levels were two to three orders of magnitudes higher than at present (Catling et al, 2001). As iron dominated oceanic chemistry during this time and through much of Earth's history, a coupling of AOM to iron instead of sulfate has been proposed as a globally important process on early Earth (Konhauser et al, 2005;Beal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We focus on net production to conservatively reflect the amount of O 2 that would be available to participate in reactions beyond those already consuming O 2 in modern benthic ecosystems. This metric is additionally conservative in that aerobic microbial oxidation of sulfide in modern mats is not included in net production despite generating the same weathering signals under question, and in the sulfate-poor conditions of the Archean (53,54), phototrophic/chemolithoautotrophic sulfur oxidation would have been inhibited, leading to enhanced net O 2 production (45). Despite the term "net O 2 production," no gaseous O 2 escape is necessarily implied in our model; rather we simply consider this net O 2 as being available for further reaction with nearby reductants.…”
Section: Benthic Oxygen Oases Before the Goe: Mechanistic And Numericmentioning
confidence: 99%
“…evaporitic sulfates and carbonate-associated sulfate (e.g., Kampschulte and Strauss, 2004), and (iv) highly variable, yet frequently negative ı 34 S values in sedimentary sulfides attributed to biological sulfur cycling, notably bacterial sulfate reduction (e.g., Strauss, 1997;Canfield, 2001). Considering respective observations and underlying systematics of sulfur isotopic fractionation (reviewed, e.g., in Canfield and Raiswell, 1999;Johnston, 2011), the sedimentary records of Archean ı 34 S sulfate and ı 34 S sulfide have been regarded as generally reflecting (i) a low-sulfate ocean (Habicht et al, 2002;Crowe et al, 2014), whereas (ii) controversial views exist with respect to an early activity of biological sulfur cycling. Notably, the absence of consistently sizeable fractionations in 34 S has been regarded as evidence for a limited importance of biological sulfur cycling in Archean sedimentary surface environments (e.g., Strauss et al, 2003), despite individual reports of highly 34 S-depleted pyrite in Paleoarchean sedimentary rocks (e.g., Ohmoto et al, 1993;Shen et al, 2001Shen et al, , 2009Philippot et al, 2007;Wu and Farquhar, 2013) and the notion from molecular biology that bacterial sulfate reduction represents an ancient metabolic pathway (Shen and Buick, 2004;Blumenberg et al, 2006;Philippot et al, 2007;Ueno et al, 2008;Shen et al, 2009;Johnston, 2011).…”
Section: Multiple Sulfur Isotope Systematics and Applications To The mentioning
confidence: 99%